2002
DOI: 10.1074/jbc.m204819200
|View full text |Cite
|
Sign up to set email alerts
|

1α,25-Dihydroxyvitamin D3 Inhibits GH-induced Expression of SOCS-3 and CIS and Prolongs Growth Hormone Signaling via the Janus Kinase (JAK2)/Signal Transducers and Activators of Transcription (STAT5) System in Osteoblast-like Cells

Abstract: Growth hormone (GH) and insulin-like growth factor (IGF-1) are important regulators of longitudinal bone growth. GH regulates production of IGF-1 both in liver and bone cells. Recent data (5) indicate that the GH-regulated local production of IGF-1 in bone cells determines bone growth. Although many effects of GH on bone growth are mediated by IGF-1, experimental data (6) indicate that GH can directly influence bone cell function.GH activates several signaling pathways, among them the Janus kinase (JAK)/the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 34 publications
5
29
0
Order By: Relevance
“…However, the expression of SOCS3 in response to proinflammatory stimuli and its function in osteoblasts are unknown. Only one study shows that growth hormone can induce SOCS3 expression in osteoblasts-like cells (31). Here, we report that SOCS3 is transiently induced in response to LPS treatment of osteoblasts and contributes to the early stage inhibition of LPS-induced IL-6 expression.…”
Section: Discussionmentioning
confidence: 70%
“…However, the expression of SOCS3 in response to proinflammatory stimuli and its function in osteoblasts are unknown. Only one study shows that growth hormone can induce SOCS3 expression in osteoblasts-like cells (31). Here, we report that SOCS3 is transiently induced in response to LPS treatment of osteoblasts and contributes to the early stage inhibition of LPS-induced IL-6 expression.…”
Section: Discussionmentioning
confidence: 70%
“…In the osteoblast-like osteosarcoma cell line, UMR 106, which expresses a GH-responsive JAK2/STAT5 signalling system, pretreatment with 1,25 dihydroxy-vitamin D is associated with increased and sustained responsiveness to repeat pulses of GH stimulation. It seems that this may be due to a reduced GH-induced expression of SOCS3 and CIS (Morales et al 2002).…”
Section: Socs3mentioning
confidence: 99%
“…Means Ϯ SE derived from 3 separate experiments for each are shown (*P Ͻ 0.05 for a chance difference by ANOVA). [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], were cultured in RPMI 1640 tissue culture medium containing 10% (vol/vol) FBS, 100 IU/ml penicillin, and 100 g/ml streptomycin. The BRIN-BD11 ␤-cell line was established by electrofusion of RINm5F insulinoma cells with New England Deaconess Hospital (NEDH) rat pancreatic islet cells and shares the major features of normal pancreatic ␤-cells (35,36).…”
Section: Methodsmentioning
confidence: 99%
“…Studies using truncated and mutated GHRs have shown that the box 1 region is necessary for association and activation of JAK2 (10). Activation of JAK2 is believed to be critical for initiation of most, if not all, GH-induced signaling pathways (8,21,25,28,40,59). In addition to JAK2, the Src tyrosine kinase family has been shown to be involved in GH signaling (13,61).…”
mentioning
confidence: 99%